1994
DOI: 10.1099/0022-1317-75-1-239
|View full text |Cite
|
Sign up to set email alerts
|

Unusual amino-terminal sequence repeat characterizes the capsid protein of dasheen mosaic potyvirus

Abstract: The T-terminal region of a Florida isolate of dasheen mosaic potyvirus (DMV-LA) genome including the coat protein (CP) gene was cloned and sequenced. Protease digestion was predicted to occur between the glutamine and alanine residues at positions 79 and 80 of the 408 residue long polypeptide to produce a CP of 329 amino acids with an estimated 3//,. of 36229. Following the putative protease recognition site is a DAG sequence, which is conserved among aphid-transmitted potyviral CPs. There is an unusual and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
15
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 27 publications
3
15
0
Order By: Relevance
“…Protease cleavage sites in potyvirus polyprotein sequences for the production of the CP are Q/A, Q/S or Q/G residues (Pappu et al, 1994). DsMV-Amp1, DsMVTa1 and DsMV-Xan1 have the potential protease cleavage site at position 7 and 8, between Q/A to produce a CP of 313 amino acids (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protease cleavage sites in potyvirus polyprotein sequences for the production of the CP are Q/A, Q/S or Q/G residues (Pappu et al, 1994). DsMV-Amp1, DsMVTa1 and DsMV-Xan1 have the potential protease cleavage site at position 7 and 8, between Q/A to produce a CP of 313 amino acids (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Partial sequence characterization of DsMV infecting Colocasia (Pappu et al,1994), Xanthosoma (Reyes et al, 2009) and Zantedeschia (Chen et al, 2001) and complete genome sequence from Zantedeschia have been reported (Chen et al, 2001). However no sequence information of DsMV from A. paeoniifolius, C. esculenta, and X. sagittifolium in India has so far been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has been presented recently that unequal recombination within the genome has contributed to the evolution of the coat protein of dasheen mosaic potyvirus (Pappu et al, 1994). It has also been found that differences in length of the N-terminal portion of the coat protein of different potyvirus species result from repetitions that are up to 17 amino acids in length (Ward et al, 1995).…”
mentioning
confidence: 99%
“…Repetition of a sequence unit of this size is unlikely to have arisen by slippage (Levinson & Gutman, 1987) and, in eukaryotes, would be most likely to have arisen by unequal crossingover. Thus, it seems possible that the sequence is evidence of intragenomic recombination in potyviruses (Pappu et al, 1994). However, the repetitive sequence region of dasheen mosaic virus extends beyond this region of tandem repetition and the individual repeats themselves are internally repetitious.…”
mentioning
confidence: 99%
See 1 more Smart Citation